Exploring stakeholders' perceptions of a task-shifting strategy for hypertension control in Ghana: a qualitative study - Juliet Iwelunmor; Joyce Gyamfi; Jacob Plange-Rhule; Sarah Blackstone; Nana Kofi Quakyi; Michael Ntim; Ferdinand Zizi; Kwasi Yeboah-Awudzi; Alexis Nang-Belfubah; Gbenga Ogedegbe (BMC, 2017)
Abstract Background The purpose of this study was to explore stakeholders' perception of an on-going evidence-based task-shifting strategy for hypertension (TASSH) in 32 community health centers and district hospitals in Ghana. Methods Using focus group discussions and in-depth interviews, qualitative data were obtained from 81 key stakeholders including patients, nurses, and site directors of participating community health centers involved in the TASSH trial. Qualitative data were analyzed using open and axial coding techniques. Results Analysis of the qualitative data revealed three themes that illustrate stakeholders' perceptions of the ongoing task-shifting strategy for blood pressure control in Ghana and they include: 1) awareness and understanding of the TASSH program; 2) reasons for participation and non-participation in TASSH; and 3) the benefit and drawbacks to the TASSH program. Conclusion The findings support evidence that successful implementation of any task-shifting strategy must focus not only on individual patient characteristics, but also consider the role contextual factors such as organizational and leadership factors play. The findings also demonstrate the importance of understanding stakeholder's perceptions of evidence-based task-shifting interventions for hypertension control as it may ultimately influence the sustainable uptake of these interventions into "real world" settings.